2013
DOI: 10.3126/ijim.v1i2.7399
|View full text |Cite
|
Sign up to set email alerts
|

Microbial assessment of bottled drinking water of Kathmandu valley

Abstract: ABSTRACT¬¬¬¬¬¬¬¬¬¬¬¬¬¬¬¬¬¬¬¬¬INTRODUCTION: Due to increased demand and consumption of bottled water in Kathmandu valley, there has been a growing concern about the microbiological quality of this product. The objective of this study was to assess the microbial contamination of heterotrophs and total coliform.MATERIALS AND METHODS: This cross sectional study was done in randomly selected 30 different commercial brand of bottled water available in commercial market of Kathmandu valley, Nepal. Total coliform and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 3 publications
2
17
1
Order By: Relevance
“…Unlike our study, as reported in the previous studies done in Nepal, only 10% to 80% of the bottled water samples were free from microbial (Timilshina, et al, 2012;Rai, et al, 2015;Pant, et al, 2016;Maharjan, et al, 2018). In studies done in India, the acceptability of bottled water samples based on the bacteriological parameter ranged from 55% (Gangil, et al, 2013) , 60% (Jeena, et al, 2006;Jain, et al, 2012), 62.5% (Joseph, et al, 2018), 66.7% (Venkatesan, et al, 2014), 73.33% (Bency, et al, 2010), 83% (Sharma & Kaur, 2015) to even 100% (Singla, et al, 2014).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Unlike our study, as reported in the previous studies done in Nepal, only 10% to 80% of the bottled water samples were free from microbial (Timilshina, et al, 2012;Rai, et al, 2015;Pant, et al, 2016;Maharjan, et al, 2018). In studies done in India, the acceptability of bottled water samples based on the bacteriological parameter ranged from 55% (Gangil, et al, 2013) , 60% (Jeena, et al, 2006;Jain, et al, 2012), 62.5% (Joseph, et al, 2018), 66.7% (Venkatesan, et al, 2014), 73.33% (Bency, et al, 2010), 83% (Sharma & Kaur, 2015) to even 100% (Singla, et al, 2014).…”
Section: Discussioncontrasting
confidence: 99%
“…The Department of Food Technology and Quality Control (DFTQC), Nepal has already taken actions against different bottled water International Journal of Environment ISSN 2091-2854 3 | P a g e companies for not maintaining the hygienic condition as well as for not following the standard production practices (Kathmandu Post, 2016;Kathmandu Post, 2018). Several studies done in the past in Nepal (Timilshina, et al, 2012;Pant, et al, 2016) and other parts of the world (Bharath, et al, 2003;Cidu, et al, 2011;Varga, 2011;Gangil, et al, 2013) have revealed the contamination of bottled water with various physicochemical and microbial agents. The processing plants are designed to remove a broad range of contaminants such as biological agents, dissolved gases, turbidity, iron, ammonia, arsenic, colour, and different chemical compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Bottled water may be in distribution at elevated temperature and poor storage condition for several weeks which may adversely affects its quality. Similar studies conducted by Magda et al (2008) in Egypt, Liee (2011) in South Africa, Oyedeji (2012) in Ile Ife, Nigeria, Sasikaran et al (2012) in Sri Lanka as well as Timilshina et al (2012) in Kathmandu , all recorded high Aerobic Mesophilic Count range that exceeded the 100cfu/ml standard of bottled drinking water as recorded by the researcher. Coliform count of 5% from brand A and C above the zero permissible limits was found to be unfit for human consumption as it exceeds the 0 cfu /100ml of excellent treated bottled water.…”
Section: Discussionsupporting
confidence: 82%
“…(10) In a similar study done by Timilshina et al; at 2012, total coliform had been reported slightly lower (56.6%) than this study. (11) E.coli was predominant (54.2%) bacteria among coliforms which notified a poor sanitary activity on commercially selling water bottle and 45.8% water sample had Enterobacter spps and one fifth of the water sample was found to be contaminated by Pseudomonas spp and Streptococcus fecalis. A study done in Kathmandu, Nepal had reported the lower presence of E. coli and Enterobacter spp on drinking jar water sample than this study.…”
Section: Bacterial Analysismentioning
confidence: 99%